Mid-term outcome of bilateral fragility fractures of the sacrum after bisegmental transsacral stabilization versus spinopelvic fixation: a prospective study of two minimally invasive fixation constructs. (1st March 2021) - Mendel, Thomas; Schenk, Philipp; Ullrich, Bernhard Wilhelm; Hofmann, Gunther Olaf; Goehre, Felix; Schwan, Stefan; Klauke, Friederike
Abstract : Aims: Minimally invasive fixation of pelvic fragility fractures is recommended to reduce pain and allow early mobilization. The purpose of this study was to evaluate the outcome of two different stabilization techniques in bilateral fragility fractures of the sacrum (BFFS). Methods: A non-randomized, prospective study was carried out in a level 1 trauma centre. BFFS in 61 patients (mean age 80 years (SD 10); four male, 57 female) were treated surgically with bisegmental transsacral stablization (BTS; n = 41) versus spinopelvic fixation (SP; n = 20). Postoperative full weightbearing was allowed. The outcome was evaluated at two timepoints: discharge from inpatient treatment (TP1; Fitbit tracking, Zebris stance analysis), and ≥ six months (TP2; Fitbit tracking, Zebris analysis, based on modified Oswestry Disability Index (ODI), Majeed Score (MS), and the 12-Item Short Form Survey 12 (SF-12). Fracture healing was assessed by CT. The primary outcome parameter of functional recovery was the per-day step count; the secondary parameter was the subjective outcome assessed by questionnaires. Results: Overall, no baseline differences were observed between the BTS and SP cohorts. In total, 58 (BTS = 19; SP = 39) and 37 patients (BTS = 14; SP = 23) could be recruited at TP1 and TP2, respectively. Mean steps per day at TP1 were median 308 (248 to 434) in the BTS group and 254 (196 to 446) in the SP group. At TP2, median steps per day were 3, 759 (2, 551 to 3, 926) in the BTS group and 3, 191 (2, 872 to 3, 679) in the SP group, each with no significant difference. A significant improvement was observed in each group (p < 0.001) between timepoints. BTS patients obtained better results than SP patients in ODI (p < 0.030), MS (p = 0.007), and SF-12 physical status (p = 0.006). In all cases, CT showed sufficient fracture healing of the posterior ring. Conclusion: Both groups showed significant outcome improvement and sufficient fracture healing. Both techniques can be recommended for BFFS, although BTS was superior with respect to subjective outcome. Step-count tracking represents a reliable method to evaluate the mobility level. Cite this article: Bone Joint J  2021;103-B(3):462–468.